2003
DOI: 10.1287/mnsc.49.10.1387.17309
|View full text |Cite
|
Sign up to set email alerts
|

Models for Supply Chains in E-Business

Abstract: S upply chain management is likely to play an important role in the digital economy. In this paper, we first describe major issues in traditional supply chain management. Next, we focus our attention on the supply chain issues of visibility, supplier relationships, distribution and pricing, customization, and real-time decision technologies that have risen to importance with the prevalence of e-business. We present an overview of relevant analytical research models that have been developed in these areas, disc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
223
0
2

Year Published

2005
2005
2019
2019

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 403 publications
(225 citation statements)
references
References 47 publications
0
223
0
2
Order By: Relevance
“…A number of researchers have contributed to the development of design strategy for forward supply chains and our models are motivated by this work (Swaminathan and Tayur 2003, Fisher 1997, Lee and Whang 1999, Lee and Tang 1997, Feitzinger and Lee 1997. We are able to confirm a set of design principles for reverse supply chains.…”
Section: Supply Chain Design Strategymentioning
confidence: 99%
“…A number of researchers have contributed to the development of design strategy for forward supply chains and our models are motivated by this work (Swaminathan and Tayur 2003, Fisher 1997, Lee and Whang 1999, Lee and Tang 1997, Feitzinger and Lee 1997. We are able to confirm a set of design principles for reverse supply chains.…”
Section: Supply Chain Design Strategymentioning
confidence: 99%
“…These models typically assume that excess demand may be lost, possibly with additional penalties, and excess supply may be sold in a "salvage market" (which may be thought of as similar to a spot market, but at a fixed price). A basic review of these results can be found in Cachon (2003), Kleindorfer and Wu (2003), Swaminathan and Tayur (2003). Linking this literature with the options framework here, several papers (Araman et al 2002, Barnes-Schuster et al 2002, Shi et al 2002 show that buy-back contracts, quantity-flexible contracts, information-sharing contracts, as well the classic newsvendor model and others are all special cases of two-part-tariff options (however, these papers only treat the single-seller, single-buyer case).…”
Section: Literature Reviewmentioning
confidence: 99%
“…[18] are the most outstanding ones. Many of these authors' analytical models provide satisfactory results, although some methodological difficulties could arise from the structure of the models developed when it comes to applying them, as well as considerable constraints in their field of application, owing to some rigid conditions established, such as, for example, the fact that they concentrate only on one parameter [19]. It should also be noted that the article by Lee et al [20] provides an excellent approach to the analysis of the causes and potential solutions of the Bullwhip effect.…”
Section: Introductionmentioning
confidence: 99%